Down-regulated expressions of PPARγ and its coactivator PGC-1 are related to gastric carcinogenesis and Lauren’s classification in gastric carcinoma - Yu, Han; Xin, Yan (Chinese Journal of Cancer Research; Vol 25, No 6 (December 26, 2013): Chinese Journal of Cancer Research, 2013)
Objective: To explore the relationship between peroxisome proliferator activated receptor-gamma (PPARγ) and peroxisome proliferator-activated receptor-gamma coactivator-1 (PGC-1) expression in gastric carcinoma (GC), and analyze their correlations with clinicopathological features and clinical outcomes of patients. Methods: The two-step immunohistochemical method was used to detect the expression of PPARγ and PGC-1 in 179 cases of GC, and 108 cases of matched normal gastric mucosa. Besides, 16 cases of fresh GC specimens and corresponding normal gastric mucosa were detected for PGC-1 expression with Western blotting. Results: The positive rates of PPARγ and PGC-1 expression were significantly lower in GC (54.75%, 49.16%) than in normal gastric mucosa (70.37%, 71.30%), respectively (P